If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 10 = 5b + -56 Reorder the terms: 10 + 3b = 5b + -56 Reorder the terms: 10 + 3b = -56 + 5b Solving 10 + 3b = -56 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 10 + 3b + -5b = -56 + 5b + -5b Combine like terms: 3b + -5b = -2b 10 + -2b = -56 + 5b + -5b Combine like terms: 5b + -5b = 0 10 + -2b = -56 + 0 10 + -2b = -56 Add '-10' to each side of the equation. 10 + -10 + -2b = -56 + -10 Combine like terms: 10 + -10 = 0 0 + -2b = -56 + -10 -2b = -56 + -10 Combine like terms: -56 + -10 = -66 -2b = -66 Divide each side by '-2'. b = 33 Simplifying b = 33
| 7f-6=36 | | 480=12x | | 2(x+9)=4b | | n+11=52 | | 5x^2+6=411 | | -4(2x-3)=-36 | | 7x+4=5x+2+2x | | lx-4l=-1 | | 15x-11=10+15x | | 6=14-2(x-2) | | 14-(-16)= | | 6k-sz=12 | | 12x-8=19+3x | | -2x=-4+24 | | 3(2x+6)-4=14 | | 7(y-5)=21 | | -(18+x)=-4+8x | | 3x+6+9x-8= | | 19=3(x-1) | | 9+10= | | 6y^2+11y+4=g | | 20=6x+2 | | 4a+3a-2= | | 5+6-(8-6)= | | 9x-11=5x+13 | | 4-7x=2x+3 | | 12+2x=5x+27 | | .75b=15 | | 125-x^2=0 | | 11(7x)=5(2x)+13 | | .9y=-36 | | 10B-6B-3=9 |